PECULIARITIES OF HEALTH OF INFANTS BORN AFTER IN VITRO FERTILIZATION (REVIEW) - T. M. Klimenko; K.V. Pokotylo; K.O. Goliuk (Bukovynian State Medical University, 2019)
Infertility is a major health and social problem of modern society. In vitro fertilization (IVF) is the advanced treatment for most forms of female and male infertility. Pregnancy and childbirth, occurred as a result of the use of assisted reproductive technologies, have a high risk of complications, and the clinical state of the newborns requires increased attention and timely assistance.